The Invasive Bank Vole (Myodes glareolus): A Model System for Studying Parasites and Ecoimmunology during a Biological Invasion - McManus, Andrew; Holland, Celia V.; Henttonen, Heikki; Stuart, Peter (MDPI AG, 2021)
The primary driver of the observed increase in emerging infectious diseases (EIDs) has been identified as human interaction with wildlife and this increase has emphasized knowledge gaps in wildlife pathogens dynamics. Wild rodent models have proven excellent for studying changes in parasite communities and have been a particular focus of eco-immunological research. Helminth species have been shown to be one of the factors regulating rodent abundance and indirectly affect disease burden through trade-offs between immune pathways. The Myodes glareolus invasion in Ireland is a unique model system to explore the invasion dynamics of helminth species. Studies of the invasive population of M. glareolus in Ireland have revealed a verifiable introduction point and its steady spread. Helminths studies of this invasion have identified enemy release, spillover, spillback and dilution taking place. Longitudinal studies have the potential to demonstrate the interplay between helminth parasite dynamics and both immune adaptation and coinfecting microparasites as M. glareolus become established across Ireland. Using the M. glareolus invasion as a model system and other similar wildlife systems, we can begin to fill the large gap in our knowledge surrounding the area of wildlife pathogen dynamics.
Keywords: biological invasion; emerging infectious diseases; parasite dynamics